Vitamin C and thiamine are associated with lower mortality in sepsis. Issue 1 (July 2020) - Byerly, Saskya; Parreco, Joshua P.; Soe-Lin, Hahn; Parks, Jonathan J.; Lee, Eugenia E.; Shnaydman, Ilya; Mantero, Alejandro; Yeh, D. Dante; Namias, Nicholas; Rattan, Rishi
Abstract : BACKGROUND: The efficacy of vitamin C (VitC) and thiamine (THMN) in patients admitted to the intensive care unit (ICU) with sepsis is unclear. The purpose of this study was to evaluate the effect of VitC and THMN on mortality and lactate clearance in ICU patients. We hypothesized that survival and lactate clearance would be improved when treated with thiamine and/or VitC. METHODS: The Philips eICU database version 2.0 was queried for patients admitted to the ICU in 2014 to 2015 for 48 hours or longer and patients with sepsis and an elevated lactate of 2.0 mmol/L or greater. Subjects were categorized according to the receipt of VitC, THMN, both, or neither. The primary outcome was in-hospital mortality. Secondary outcome was lactate clearance defined as lactate less than 2.0 mmol/L achieved after maximum lactate. Univariable comparisons included age, sex, race, Acute Physiology Score III, Acute Physiology and Chronic Health Evaluation (APACHE) IVa score, Sequential Organ Failure Assessment, surgical ICU admission status, intubation status, hospital region, liver disease, vasopressors, steroids, VitC and THMN orders. Kaplan-Meier curves, logistic regression, propensity score matching, and competing risks modeling were constructed. RESULTS: Of 146, 687 patients from 186 hospitals, 7.7% (n = 11, 330) were included. Overall mortality was 25.9% (n = 2, 930). Evidence in favor of an association between VitC and/or THMN administration, and survival was found on log rank test (all p < 0.001). After controlling for confounding factors, VitC (adjusted odds ratio [AOR], 0.69 [0.50–0.95]) and THMN (AOR, 0.71 [0.55–0.93]) were independently associated with survival and THMN was associated with lactate clearance (AOR, 1.50 [1.22–1.96]). On competing risk model VitC (AOR, 0.675 [0.463–0.983]), THMN (AOR, 0.744 [0.569–0.974]), and VitC+THMN (AOR, 0.335 [0.13–0.865]) were associated with survival but not lactate clearance. For subgroup analysis of patients on vasopressors, VitC+THMN were associated with lactate clearance (AOR, 1.85 [1.05–3.24]) and survival (AOR, 0.223 [0.0678–0.735]). CONCLUSION: VitC+THMN is associated with increased survival in septic ICU patients. Randomized, multicenter trials are needed to better understand their effects on outcomes. LEVEL OF EVIDENCE: Therapeutic Study, Level IV. Abstract : Supplemental digital content is available in the text.